INVESTIGATING THE CORRELATION BETWEEN TIME MANAGEMENT AND ACCOMPLISHING THE HIGHEST HONOR OF ACADEMIC ACHIEVEMENT IN PMPBI UNJ THE CLASS OF 2019 STUDENTS - Elita Pertiwi (IJELAL (International Journal of English Learning and Applied Linguistics), 2021)
ABSTRACT: Time management is essential, and it may affect an individual's overall performance and achievements. Research has shown that all the time management behaviors are positively related to academic achievement. This study aims to measure the level of time management possessed by PMPBI UNJ the year of 2019 students and find out the correlation between the level of time management and the success of achieving a Summa Cum Laude honorary degree. The primary data collection for this study is through an online questionnaire survey. Data were analyzed using descriptive statistics, and the presentations were made in tables and figures to some extent. The result shows that 55% of the participants possess a moderate level time management score, while 45% of the participants possess high-level time management scores. No participants have a low-level time management score. Furthermore, the result also reveals that the level of time management (High or Moderate Level) correlates with the success of achieving a Summa Cum Laude honorary degree for students of the PMPBI UNJ class of 2019. Lastly, the results also show that Short-Range planning, and Time Attitudes, each variable correlates with the success of achieving a Summa Cum Laude honorary degree. However, the results show that Long-Range planning does not correlate with the success of achieving a Summa Cum Laude honorary degree. Keywords: time management level, short-range, time attitude, long-range, students’ achievement, Summa Cum Laude.